Usability and User Experience Test on the Muezzin and Khatib Scheduling Mobile Application Using SUS and User Experience Questionnaire (Case Study: Al Abroor Mosque) - Rahmadi Wijaya; Cahyana Cahyana; Bambang Pudjoatmodjo (IJAIT (International Journal of Applied Information Technology), 2021)
One of the Dewan Kemakmuran Masjid (committee to serve public service in a mosque) main task is to provide prayer facilities in a mosque, such as managing schedules for muezzin and imam salat. Most of the time, the plan is executed manually. Moreover, preparing the schedule is not easy. It needs cautious and excessive effort as DKM members should be careful not to make an unbalanced schedule for each muezzin/ khatib. It is also an error-prone process since putting the unavailable person in the schedule slot is possible. To overcome the condition, we build a mobile application for managing schedules for muezzin and imam salat. The application has been tested with usability testing and a user experience questionnaire. The results from both testing tools yield excellent results; the application could implement and comfortably used for managing schedules. From the result, it can be inferred that Al Aboor meets the criteria for a good mobile application and can be developed further.